Development of Chitosan-Based Hydrogel Containing Polyvinyl Alcohol, Cellulose and ZnO Nanoparticles for Potential Biomedical Applications - Dewanjee, Suman; Ahmed, Hasan; Tanvir, Mohammad Ali; Ali, Muttakee Bin; Dipa, Safia Aktar; Imran, Md Ibrahim Al (Dhaka University Journal of Science, 2025)
Waste materials such as chitosan-rich shrimp shells and cellulose-containing sugarcane bagasse are discarded in substantial quantities worldwide. These by-products hold untapped potential for creating sustainable biomaterials, such as hydrogels, for biomedical applications. This research bridges sustainable development and biomedical engineering by producing a biocompatible, thermally stable, mechanically optimized, and infection-resistant hydrogel. The study examines a composite hydrogel formulated from chitosan, polyvinyl alcohol (PVA), Tannic acid (TA),and zinc oxide nanoparticles (ZnONP), with glutaraldehyde and gelatin powder as a cross-linking agent. Glutaraldehyde enhances cross-linking with chitosan’s amine groups, improving the hydrogel’s thermal stability, while ZnONP functionalization enhances its antibacterial properties. Comprehensive evaluations covered structural integrity, cell viability, swelling ratio, water vapor transmission rate, pore size, and mechanical and thermal properties. Analytical techniques such as FTIR and XRD confirmed favorable swelling ratios, porosity, and water vapor permeability, highlighting the hydrogel’s suitability for wound dressings. By achieving optimal degrees of swelling (DSR) and water vapor transmission rates (WVTR), the chitosan-based PVA/cellulose/ZnONP hydrogel demonstrates promise for advanced wound healing applications, supporting both skin restoration and infection control. The novelty lies in the way of approach to bring sustainability and biomedical engineering together. Dhaka Univ. J. Sci. 73(1): 43-49, 2025 (January)